Quantum Interferometry in Phase Space Theory and Applications - Suda, Martin (Springer Berlin Heidelberg : Imprint: Springer, 2006)
Quantum Interferometry in Phase Space is primarily concerned with quantum-mechanical distribution functions and their applications in quantum optics and neutron interferometry. In the first part of the book, the author describes the phase-space representation of quantum optical phenomena such as coherent and squeezed states. Applications to interferometry, e.g. in beam splitters and fiber networks, are also presented. In the second part of the book, the theoretical formalism is applied to neutron interferometry, including the dynamical theory of diffraction, coherence properties of superposed beams, and dephasing effects.